2020
DOI: 10.1007/s00401-020-02140-y
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of diffusion-weighted imaging-positive lesions in cerebral amyloid angiopathy

Abstract: Small subclinical hyperintense lesions are frequently encountered on brain diffusion-weighted imaging (DWI) scans of patients with cerebral amyloid angiopathy (CAA). Interpretation of these DWI+ lesions, however, has been limited by absence of histopathological examination. We aimed to determine whether DWI+ lesions represent acute microinfarcts on histopathology in brains with advanced CAA, using a combined in vivo MRI-ex vivo MRI-histopathology approach. We first investigated the histopathology of a punctate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…AIS as the primary manifestation of CAA is likely to be underdiagnosed since DWI lesions in CAA patients are often discussed as an epiphenomenon of CAA. Yet, a former study revealed that 130 DWI and T2* lesions examined histopathologically were in 100% acute microinfarcts [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIS as the primary manifestation of CAA is likely to be underdiagnosed since DWI lesions in CAA patients are often discussed as an epiphenomenon of CAA. Yet, a former study revealed that 130 DWI and T2* lesions examined histopathologically were in 100% acute microinfarcts [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral microinfarcts manifest as small ovoid or round high intensity areas in the subcortex and cortex on diffusion-weighted MRI [ 38 ]. Analyses of autopsied brains with CAA cases have identified diffusion-weighted imaging-positive lesions that represent acute infarcts [ 39 ].…”
Section: Diagnosis Of Caa: Markers Characteristic Features and Techniquesmentioning
confidence: 99%
“…The development of magnetic resonance imaging (MRI) technology has provided the most potent approach to understanding the etiology of hemorrhage. Diffusion-weighted imaging (DWI) hyperintensities distant from the hematoma were considered to be acute ischemic lesions, [1][2][3][4][5] which were identified in 11-41% of patients with acute ICH. 2,4,[6][7][8] They further aggravated brain injury.…”
Section: Introductionmentioning
confidence: 99%